2019
DOI: 10.1002/jcsm.12376
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting in patients with end‐stage renal disease or early‐stage lung cancer: common mechanisms at work

Abstract: Background Loss of muscle mass worsens many diseases such as cancer and renal failure, contributes to the frailty syndrome, and is associated with an increased risk of death. Studies conducted on animal models have revealed the preponderant role of muscle proteolysis and in particular the activation of the ubiquitin proteasome system (UPS). Studies conducted in humans remain scarce, especially within renal deficiency. Whether a shared atrophying programme exists independently of the nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
0
26
1
Order By: Relevance
“…Interestingly, E3 ligases auto-ubiquitinate, which makes them more susceptible to proteasomal degradation, thus requiring continuous transcriptional replenishment. Two muscle-specific E3 ubiquitin ligases, muscle ring finger1 (MuRF1/Trim63) and muscle atrophy F-box (Atrogin-1/MAFbx), are dramatically upregulated during various types of atrophy [ 68 , 69 , 70 , 71 ]. Moreover, mice deficient in MuRF1 and Atrogin-1 are partially protected against disuse atrophy [ 69 ].…”
Section: Regulators Of Proteolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, E3 ligases auto-ubiquitinate, which makes them more susceptible to proteasomal degradation, thus requiring continuous transcriptional replenishment. Two muscle-specific E3 ubiquitin ligases, muscle ring finger1 (MuRF1/Trim63) and muscle atrophy F-box (Atrogin-1/MAFbx), are dramatically upregulated during various types of atrophy [ 68 , 69 , 70 , 71 ]. Moreover, mice deficient in MuRF1 and Atrogin-1 are partially protected against disuse atrophy [ 69 ].…”
Section: Regulators Of Proteolysismentioning
confidence: 99%
“…Additional novel E3 ubiquitin ligases belonging to the Skp1–cullin-1–FBOX E3 ubiquitin ligase complex (SCF) have been identified and found to contribute to muscle loss during fasting, denervation, and cancer cachexia [ 59 , 85 , 86 , 87 ]. MUSA1 ( Fbxo30 ) [ 59 , 71 ], SMART ( Fbxo21 ), and Fbxo31 [ 85 ] are all induced during atrophic conditions and their inhibition materially reduces muscle wasting. Moreover, a recent study found SMART and Fbxo31 to be upregulated in a rodent model of critical illness-induced myopathy, and this upregulation was blunted by passive mechanical loading [ 88 ].…”
Section: Regulators Of Proteolysismentioning
confidence: 99%
“…In animal models of CKD-induced muscle atrophy, studies of muscle biopsies have shown an increase in the 14kDa actin level, a "footprint" of caspase 3 activity [5], increased expression of E3 ligases such as the muscle-specific E3 ligases MuRF1 and MAFbx [9,10], and proteasome subunits [11]. In humans, activation of the UPS is evidenced by an increased expression of several E3 ligases in the muscle of hemodialysis patients [4]. However, it is not possible to perform a muscle biopsy in all patients to detect the activation of UPS.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in muscle mass is due to an imbalance in protein synthesis and proteolysis in favor of the latter [ 2 ]. The ubiquitin-proteasome proteolytic system (UPS) is crucial for the atrophying process, notably in chronic kidney disease (CKD) [ 3 , 4 ]. The first step in myofibrillar protein degradation is thought to be activation of caspase 3 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…(6,7) Furthermore, the mRNA levels of ATF4 and CHOP are increased in skeletal muscle in hemodialysis patients. (8) Ectopic accumulation of excess lipids, called lipotoxicity, plays a central role in the pathogenesis of cardio-metabolic diseases. (9) On the other hand, the quality of lipids (lipoquality), which is defined as the functional features of diverse lipid species, has recently been a focus of study in the pathology of metabolic diseases.…”
mentioning
confidence: 99%